Effects of the use of self-learning kits on the achievement of students in high school science II - Advincula, Ester C. (1978)
This study focused on the achievement of science students using Self-Learning Kits (SLK) with that of students using the textbook, Biology for Philippine High Schools, The Relationship of Living Things. Findings indicated that there was a significant difference between the achievement of science students using SLKs as instructional materials and students using the textbook.